Canonisation of New Martyrs and Confessors of 20th Century in the Russian Orthodox Church - Solovejs, Mikus (European Journal of Mental Health, 2013)
At present, the Russian Orthodox Church faces a serious evaluation of the history of the Church in the 20th century. As it is known, the 20th century for the Russian Orthodox Church was a tragic one. The communist regime realized not only mass physical and spiritual terror, but created falsifi cations and myths of history as well. One of the main ideals of the communist regime was the extermination of Christian faith and the aspersion of religious practice. Therefore one of the essential steps in the direction of renewal of historical truth was the canonization of the victims – the new martyrs and confessors – of communist terror in the Local Councils of the Moscow Patriarchy. Similarly, saints have always served as examples of religious practice. That would serve as well as a reminder about the goals of human life, the value of life and the highest example for respect of a person. In the fi rst part of the article, the bloodiest pages of history of the Russian Church are looked at, when the Bolshevik, coming into power, started the persecution of the Orthodox Church. The article observes the persecutions commenced by the Soviet state in the 1918–1941 period, as during this time the most ruthless persecutions took place, and the martyrs of this age form the greatest proportion in number within the body of holy new-martyrs and confessors of the 20th century. Next, the relevance of studying the archive documents and the methodology of analysis are examined, as the process of canonization is based on the study and analysis of historical facts; the conformity of the person being canonized is rigorously examined. The second part of the article reviews the very process of canonization as well as the chronological sequence in accordance with the decisions of the Synod of the Russian Orthodox Church. Similarly, the decisions of the Synod regarding the veneration practice of saints are attached. The end of the article focuses on the tasks that derive from the fact of canonization.